Pengaruh Model Pembelajaran Kooperatif Tipe Snowball Throwing Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Administrasi Umum Kelas X OTKP Di SMK Ketintang Surabaya - Sonia Adelina; Brillian Rosy (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
This study aims to determine the effect of snowball throwing cooperative learning models on student learning outcomes in class X OTKP on the basic competence of implementing communication at work in SMK Ketintang Surabaya. This type of experimental research uses a quasi experimental design with a non-equivalent control group design. The research sample is students of class X OTKP2 and X OTKP3, each consisting of 30 students. Data collection techniques with documentation, interviews, tests, and observations. The research instrument uses the cognitive realm. Data analysis used normality test, homogeneity test, t-test and gain score. The results of this study indicate the results of the t test obtained the value of tcount> ttable (6.579> 2.001) and the difference (gain score) of the pre-test and post-test values obtained that tcount> ttable (7.101> 2.001) so that the average difference from the pre-value test and post-test experimental class 0.62 is greater than the value of the pre-test and post-test control class of 0.33. It can be concluded that the cooperative learning model of snowball throwing type affects the learning outcomes of Grade X OTKP students at SMK Ketintang.